Insecure Land Tenure in Rural Areas of Latin America - Thome, Joseph (1971)
The purpose of the following article is to analyze the problem of land tenure insecurity in rural areas of Latin America. This insecurity translates into the lack of a legal title that accredits a legitimate property right. The author argues that this problem has its origin in the deficiency of the registry systems, the limitation of agrarian reform programs and, mainly, the need for efficient legislation on the subject. This scenario has been affecting an incalculable number of peasants who, in most cases, occupy land without a secure title of ownership and, consequently, without the privilege of a formal registry and the possible exercise of a property right that has been denied to them for historical, legal and political reasons. The author mentions that a possible solution lies in a legislative modification that would help in the legal procedures for granting and registering property titles, as well as strengthening agrarian reform and the training of officials in charge of granting titles.